Economics of Business Research on Customers’ Retention and Sales Improvement in Supermarkets - Adebayo, OLOIDI Gabriel; Oladimeji, OLUWALANA Lucas (IJRDO - Journal of Business Management, 2015)
In recent times, the supermarkets around the globe have been so supper among markets that theiractivities have caught the mercy of various professionals and have attracted much attention. Thecompetitive eloquence is an embellishment of the mystery surrounding their survival. This studyhas aimed at succinctly contributing to successful operation of these supermarkets throughbusiness research. A particular supermarket was taking as a case study, which can be adjustablyapplied to any other supermarket. A business research was initiated, collecting data on variousbusiness activities, customers and competitors. The recency, frequency and monetary (RFM)model was used to sieve various customers who can score RFM of about 280 out of a total of555 thereby inferring customers with loyalty and hence are those that matter. The regressionmodel was used to initiate a sales forecast from the research data and subsequently where thesales target is derived. Other various aspect of the philosophy of retaining, and winning morecustomers, dovetailing to improving sales, from experts and professional, formed the dynamicforce behind the achievement of the business research outcome. It is recommended thatsupermarket managers should study the findings in the paper and apply to their situation givingthe latitude for necessary adjustments.